What Makes Nigerian Manufacturing Firms Take Action on HIV/AIDS? - Rosen, Sidney (World Bank, Washington, DC, 2012)
The results of a 2001 survey of Nigerian manufacturing firms, underscore the importance of giving business managers, both a reason, and the means to take action on the implications of HIV/AIDS. Using regression methods to analyze which characteristics of the firms affected the probability about taking action on the epidemic, five variables, statistically predicted such action: known working individual, currently an HIV-positive; deceased individual, or who no longer works with the firm due to HIV/AIDS; information received by the firm on HIV/AIDS in the last year; the industrial importance of the firm; and, an on-site medical clinic at the firm. These findings indicate that first hand experience on the epidemic, is a determining factor for behavioral change, consistent with findings in both developed, and developing countries. Thus, it is suggested that conducting voluntary, anonymous HIV prevalence surveys in the workforce, may become the practice that prompts managers to take action, and, findings also supported the efforts that would promote counseling, and testing, as an intervention to reduce risky behavior, therefore helping prevent the spread of the disease.